2021
DOI: 10.1002/ajp.23272
|View full text |Cite
|
Sign up to set email alerts
|

Social aging in male and female Barbary macaques

Abstract: Aging brings about notable changes in sociality, with an increasing focus on essential partners in both humans and nonhuman primates. Several studies have shown that older nonhuman primates have fewer social partners and shift their types of interactions. The majority of these studies, however, involved only female individuals.Much less is known about the trajectory of social aging in males. We collected 2180 h of focal observation data in a large age-heterogeneous sample of 34 male and 50 female Barbary macaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…Investigating demographic structuring, selective disappearance, and spatial behaviours in primate populations (e.g. 12,27,43 ) may shed an important light on the different drivers of age-related changes in sociality across mammals and other taxa. Ultimately, broadening the selection of study organisms for age-sociality interactions to include those a wider variety of fluid and rigid social systems could help to develop generalisable insights about the causes and consequences of social ageing across the tree of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating demographic structuring, selective disappearance, and spatial behaviours in primate populations (e.g. 12,27,43 ) may shed an important light on the different drivers of age-related changes in sociality across mammals and other taxa. Ultimately, broadening the selection of study organisms for age-sociality interactions to include those a wider variety of fluid and rigid social systems could help to develop generalisable insights about the causes and consequences of social ageing across the tree of life.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if an animal forms relationships when it is young which are not replaced when those contacts die 25,26 , then older animals will be less socially connected as a result. Social connectedness has recently been shown to correlate with age in chimpanzees, macaques, ibex, and marmots 12,[27][28][29][30] , but the relative roles of these spatial, demographic, and withinindividual drivers have yet to be investigated. Untangling these processes could shed a light on the relative importance of within-individual age-related behavioural changes (compared to physiological or demographic processes) in determining population structure in wild animals.…”
Section: Introductionmentioning
confidence: 99%
“…Physical deterioration is expected to lead to declines in capacity to socially interact and reduced desirability as a social partner, leading to overall declines in social connectedness due to both social withdrawal and social exclusion. [16,35,56,57] §2a(ii) energetic deficiencies Energetic deficiencies are expected to restrict an individual's movement and therefore their ability to socially engage or the likelihood of others coming into social contact, leading to reductions in the quality and quantity of social relationships. [16,35,56,57] §2a(iii) sociocognitive decline Socio-cognitive decline may facilitate reduced social engagement owing to decreased social motivation, social attention, or inability to recognize partners.…”
Section: Degree §2a(i) Physical Deteriorationmentioning
confidence: 99%
“…[16,35,56,57] §2a(ii) energetic deficiencies Energetic deficiencies are expected to restrict an individual's movement and therefore their ability to socially engage or the likelihood of others coming into social contact, leading to reductions in the quality and quantity of social relationships. [16,35,56,57] §2a(iii) sociocognitive decline Socio-cognitive decline may facilitate reduced social engagement owing to decreased social motivation, social attention, or inability to recognize partners. Old individuals may be less desirable partners as a result.…”
Section: Degree §2a(i) Physical Deteriorationmentioning
confidence: 99%
“…High measures of centrality derive from an individual's many and strong social ties and those of their direct contacts (Sosa et al, 2020). In non-human animals, centrality corresponds with greater food discovery (Paridae songbirds, Aplin et al, 2012), and has been shown to decrease with age in female yellow-bellied marmots (Blumstein et al, 2018), and in some primates (Barbary macaques, Rathke & Fischer, 2021) but not all those examined (rhesus macaques, Liao et al, 2018). In some species, embeddedness corresponds with decreased parasites and infection (Balasubramaniam et al, 2016;Duboscq et al, 2016), however, under some circumstances it can lead to greater pathogen exposure (Nunn, 2012;Page et al, 2017).…”
Section: Justification Of Social Network Measures: Functions and Changes With Agementioning
confidence: 99%